Pregnancy Outcome of Renal Transplant Recipients: Analysis of Nine Patients - Mert Turğal; Aslıhan Yazıcıoğlu; Kemal Beksaç; Özgür Özyüncü; Sinan Beksaç (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Pregnancy in renal transplant recipient was considered unsafe in the past. To date, these patients have successful pregnancy outcome. In this study, we aimed to analyze the outcome of pregnancy in kidney transplant recipients and the consequences on renal function. STUDY DESIGN: Retrospective analysis RESULTS: We found that the mean gestational age at delivery for patients were 35.22 weeks and 55.5% patients had preterm delivery and this result is higher than normal pregnant population. CONCLUSION: Pregnant women who renal transplant recipient have higher risk for preterm labor and hypertension compared normal pregnant women.